IDNLearn.com is your go-to platform for finding reliable answers quickly. Our experts provide timely and precise responses to help you understand and solve any issue you face.
Sagot :
Answer:
[tex](2x^2+2x+1)-(7x^2+2x+15)=-5x^2-14[/tex]
Step-by-step explanation:
To explain how to approach this question, I am going to place letters in the blank spaces:
[tex](ax^2+bx+c)-(dx^2+ex+f)=-5x^2-14[/tex]
First, compare the coefficients of the x² terms on both sides of the equation: [tex]a - d = -5[/tex]
Therefore, we need to choose any two numbers in place of a and d whose difference is -5:
⇒ a = 2 and d = 7 as 2 - 7 = -5.
Similarly, upon comparing the coefficients of the x terms, we can see that there is no x term on the right side of the equation. Therefore, we need to choose numbers in place of b and e for which the difference is zero. So b and e should be the same number:
⇒ b = 2 and e = 2 as 2 - 2 = 0.
Finally, compare the constant term on both sides of the equation: [tex]c - f = -14[/tex]
Therefore, we need to choose any two numbers in place of c and f whose difference is -14:
⇒ c = 1 and f = 15 as 1 - 15 = -14.
Plug in the numbers in place of the letters on the left side of the equation:
[tex](2x^2+2x+1)-(7x^2+2x+15)=-5x^2-14[/tex]
Check
Remove the brackets:
[tex]2x^2+2x+1-7x^2-2x-15=-5x^2-14[/tex]
Collect like terms:
[tex]2x^2-7x^2+2x-2x+1-15=-5x^2-14[/tex]
Combine like terms:
[tex]-5x^2-14=-5x^2-14[/tex]
Hence proving that the left and right sides of the equation are the same.
Thank you for being part of this discussion. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. IDNLearn.com is your go-to source for accurate answers. Thanks for stopping by, and come back for more helpful information.